The Role of Ombudsman in Supervising Public Services in The Land Sector - Oktobrian, Dwiki; Alisya, Nazwa Serin; Maharani , Yunita Putri; Sudrajat, Tedi (Universitas Muhammadiyah Yogyakarta, 2026)
Maladministration in public land services remains a recurring structural issue that undermines legal certainty and erodes public trust in state institutions. This article addresses two main concerns: the high volume of public complaints about poor land services and the limited influence of external oversight bodies, such as the Ombudsman, in driving systemic reform. The study aims to analyze the forms and patterns of maladministration in the land sector and assess the effectiveness of the Ombudsman's role in addressing and preventing it. Using a socio-legal approach, data were collected through semi-structured interviews and analysis of the Ombudsman's annual reports and other institutional documents. The findings show that the most frequent types of maladministration include prolonged delays, procedural irregularities, and negligence, particularly in non-regular land programs such as land registration (Pendaftaran Tanah Sistematis Lengkap – PTSL). The Ombudsman has demonstrated the ability to process complaints factually and resolve many cases, but its recommendations are non-binding and are often disregarded by the reporting agencies. In terms of prevention, the Ombudsman has initiated public service training and legal education programs, though their reach and impact remain limited.